Improving the Spelling Performance of Students Who Are Deaf and Exhibit Characteristics Consistent with Learning Disabilities - Soukup, Monica (Journal of the American Academy of Special Education Professionals, 2006)
Research has identified many strategies that are effective in helping students to improve spelling performance. Among the strategies that are cited in a review of the literature are the multi-sensory approach and See/Cover/Write/Compare approach. Using a single-subject behavioral dynamics experimental design with replication across subjects, this study demonstrated the effectiveness of a multi-sensory, See/Cover/Write/Compare intervention procedure to improve written spelling performance in students who were Deaf with characteristics consistent with Learning Disabilities (DCLD). Three students received daily tutoring sessions incorporating a multi-sensory, See/Cover/Write/Compare intervention procedure. Dependent measures addressed the spelling performance of each participant, interobserver reliability, procedural integrity, and consumer satisfaction. Each participant was evaluated in the areas of formative spelling performance, summative spelling performance, and spelling retention. Results from the data demonstrated improvement in spelling for all three participants across all spelling lists.